Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan pada PERUM BULOG Kantor Wilayah Sumatera Selatan dan Bangka Belitung - Kharisma, Bela; Aprilia, Frida; Siboro, Sonny Fransisco (CV Warnak Johanna Nusantara, 2026)
In the era of globalization and increasing business competition, improving employee performance is essential for organizational success. The Regional Office of PERUM BULOG in South Sumatra and Bangka Belitung faces challenges related to work discipline, delays in task completion, and an uncomfortable work environment. This study aims to analyze the influence of the work environment and work discipline on employee performance. The research employed a quantitative method with a descriptive-verificative approach. The population consisted of 40 employees, all of whom were included as samples using a saturated sampling technique. Data were collected through observation, Likert-scale questionnaires, and literature review, and analyzed using SPSS version 25 through validity, reliability, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results indicate that the work environment (t = 2.397 > t-table = 2.026; sig. = 0.022 < 0.05) and work discipline (t = 3.026 > t-table = 2.026; sig. = 0.004 < 0.05) have positive and significant effects on employee performance. Simultaneously, both variables contribute 38.8% to performance variation. Therefore, a conducive work environment and strong discipline can enhance employee productivity at the PERUM BULOG Regional Office of South Sumatra and Bangka Belitung.